2012
DOI: 10.1111/j.1600-0838.2012.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic anterior shoulder instability in the athlete

Abstract: Anterior glenohumeral dislocation is common among athletes and may progress to recurrent instability. The pathoanatomy of instability and specific needs of each individual should be considered to prevent unnecessary absence from sport. Traditionally, primary dislocations have been managed with immobilization followed by rehabilitation exercises and a return to sporting activity. However, arthroscopic stabilization and external rotation bracing are increasingly used to prevent recurrent instability. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 141 publications
(191 reference statements)
0
32
0
1
Order By: Relevance
“…For instance, a mixed-methods systematic literature review on support needs of family members of patients with ABI showed that families reported multiple support needs, including informational, emotional, and practical support [56]. Examples of their needs included wanting: 1) quality information about the patient’s symptoms [12,57]; brain injury care [58,59] and prognosis [60]; 2) their emotions to be taken into account by healthcare providers [61]; and 3) to participate in the patient’s care [62] and decision making [63]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, a mixed-methods systematic literature review on support needs of family members of patients with ABI showed that families reported multiple support needs, including informational, emotional, and practical support [56]. Examples of their needs included wanting: 1) quality information about the patient’s symptoms [12,57]; brain injury care [58,59] and prognosis [60]; 2) their emotions to be taken into account by healthcare providers [61]; and 3) to participate in the patient’s care [62] and decision making [63]. …”
Section: Discussionmentioning
confidence: 99%
“…For players without a history of dislocation, it is possible for return to play once their overall shoulder strength and motion return to normal. Joint rehabilitation may be achieved through the strengthening of the shoulder and periscapular muscles, but surgery is often required in recurrent dislocators to repair the torn labrum, ligaments and joint capsule 12 17 18. Traumatic anterior instability may be successfully rehabilitated after surgical intervention with a return to sport averaging 4–6 months 17.…”
Section: Shouldermentioning
confidence: 99%
“…Joint rehabilitation may be achieved through the strengthening of the shoulder and periscapular muscles, but surgery is often required in recurrent dislocators to repair the torn labrum, ligaments and joint capsule 12 17 18. Traumatic anterior instability may be successfully rehabilitated after surgical intervention with a return to sport averaging 4–6 months 17. Bracing, such as the SAWA brace and Duke-Wyre brace, may help prevent a repeated dislocation for first time dislocators during the season and if discomfort and instability continues, athletes should consider surgery postseason 12 13 19 20…”
Section: Shouldermentioning
confidence: 99%
“…Overall, these studies report a sevenfold reduction in the risk of recurrent instability after arthroscopic stabilization, when compared with nonoperative treatment for the fi rst-time dislocator [ 59 ]. A Cochrane review concluded that early surgical intervention is warranted in young adults aged less than 30 years engaged in highly demanding physical activities [ 68 ].…”
Section: Treatment Of Acute First Traumatic Dislocationsmentioning
confidence: 98%
“…After reducing the dislocation, plain radiographs are obtained to verify the adequacy of the reduction. Results concerning conservative treatment are still debatable [ 59 ]. A stable shoulder is obtained at 10 years in only half of the patients with conservative treatment [ 60 ].…”
Section: Treatment Of Acute First Traumatic Dislocationsmentioning
confidence: 98%